2016
DOI: 10.1212/wnl.0000000000003122
|View full text |Cite
|
Sign up to set email alerts
|

Diskogenic microspurs as a major cause of intractable spontaneous intracranial hypotension

Abstract: The nature of the CSF leak is a circumscribed longitudinal slit at the ventral, lateral, or dorsal dura mater. An extradural pathology, diskogenic microspurs, was the single cause for all ventral CSF leaks. These findings challenge the notion that CSF leaks in SIH are idiopathic or due to a weak dura. Microsurgery is the treatment of choice in cases with intractable SIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 31 publications
5
115
1
7
Order By: Relevance
“…We observed CSF leaks associated with degenerative changes in only two patients. Various previous studies in the literature reported disc hernia associated dural tears are more commonly in lower cervical and thoracic areas [18][19][20]. In our series, CSF leaks in two patients with disc hernia were in the cervical region.…”
Section: Discussionsupporting
confidence: 55%
“…We observed CSF leaks associated with degenerative changes in only two patients. Various previous studies in the literature reported disc hernia associated dural tears are more commonly in lower cervical and thoracic areas [18][19][20]. In our series, CSF leaks in two patients with disc hernia were in the cervical region.…”
Section: Discussionsupporting
confidence: 55%
“…Cervical and thoracic perineurial cysts are common incidental findings in normal patients, and, in isolation, the presence of such cysts does not necessarily indicate or increase the likelihood of a diagnosis of SIH if no active leakage is identified on imaging. 17,35 One series of over 500 patients identified ventral dural tears as the case of SIH in approximately one-quarter of patients. 4).…”
Section: Summary Of Important Considerations In the Approach To Sihmentioning
confidence: 99%
“…Ventral dural tears are a major source of spontaneous CSF leaks, and are often associated with calcified thoracic disk herniations or osteophytes. 17,35 One series of over 500 patients identified ventral dural tears as the case of SIH in approximately one-quarter of patients. 36 Another recently identified cause of SIH is the CSF-venous fistula.…”
Section: Summary Of Important Considerations In the Approach To Sihmentioning
confidence: 99%
“…Bunun sonucunda, özellikle hastalar dik pozisyonda iken, beyin, posterior fossadan aşağı doğru sarkar ve beyin sapı ile serebellar tonsillerin aşağı doğru yer değiştir-mesine neden olur. BOS kaçağının bildirilen nedenleri arasında, konnektif doku hastalıkları, spinal sinirlerin kök çıkışında görülen yırtıkları, Tarlov kisti, spinal kemik anomalileri ve akkiz dejeneratif disk hastalıkları bulunmaktadır (6,7) .…”
Section: Discussionunclassified